2021
DOI: 10.3389/fcell.2021.749806
|View full text |Cite
|
Sign up to set email alerts
|

JNK Mediates Differentiation, Cell Polarity and Apoptosis During Amphioxus Development by Regulating Actin Cytoskeleton Dynamics and ERK Signalling

Abstract: c-Jun N-terminal kinase (JNK) is a multi-functional protein involved in a diverse array of context-dependent processes, including apoptosis, cell cycle regulation, adhesion, and differentiation. It is integral to several signalling cascades, notably downstream of non-canonical Wnt and mitogen activated protein kinase (MAPK) signalling pathways. As such, it is a key regulator of cellular behaviour and patterning during embryonic development across the animal kingdom. The cephalochordate amphioxus is an inverteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…8A). In this study, we demonstrated that JNK signaling, a well-known apoptotic signaling [35][36][37], was involved in KIAA1324-mediated apoptosis (Fig. 4B).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…8A). In this study, we demonstrated that JNK signaling, a well-known apoptotic signaling [35][36][37], was involved in KIAA1324-mediated apoptosis (Fig. 4B).…”
Section: Discussionmentioning
confidence: 53%
“…4A). Since JNK is known to be an apoptosis regulator [35][36][37], the IPA network 1 represents that the up-regulated transcription program by N-glycosylated KIAA1324 is associated with apoptosis via JNK protein. The IPA network 2 includes many down-regulated genes and E2F1 a hub protein, which is consistent with the GRN analysis result (Supplementary Fig.…”
Section: Gene Regulatory Network Analysis Identified Key Transcriptio...mentioning
confidence: 99%
“…4A, B). In this study, we demonstrated that JNK signaling, a well-known apoptotic signaling (32,33,34), was involved in KIAA1324-mediated apoptosis (Supplementary Fig. 5).…”
Section: Discussionmentioning
confidence: 67%
“…4A). Since JNK is known to be an apoptosis regulator (32,33,34), the IPA network 1 represents that the upregulated transcription program by N-glycosylated KIAA1324 is associated with apoptosis via JNK protein. The IPA network 2 includes many down-regulated genes and E2F1 a hub protein (Fig.…”
Section: Gene Regulatory Network Analysis Identi Ed Key Transcription...mentioning
confidence: 99%